GURU PROFESIONAL SEBAGAI FAKTOR PENENTU PENDIDIKAN BERMUTU - Faujiah, Syifa; Afriza, Afriza; Andriani, Tuti (STAI Darul Qalam Tangerang, 2023)
The development of professional competence in the face of the golden Indonesian era is absolutely necessary for the success of learning and improving the quality of education. Without the development of professionalism, the learning process and the quality of education will only go on the spot. There is no innovation, and there is no creativity and no effective learning. The educational paradigm should use a new paradigm, namely quality. Quality education is born from qualified and professional teachers. Professional teachers can influence quality education. From the discussion, it can be concluded, that: 1). Professional teachers must be prepared by a quality and standardized educational higher education institution (LPTK); 2). Professional teachers must have academic qualifications, competencies, educator certification, be physically and spiritually healthy, and have the ability to realize national education goals; 3). Professional teachers as a determining factor for quality education are teachers who meet the standards of educators and education personnel, namely the creteria of pre-service education and physical and mental feasibility, as well as in-service education